Overview of CLCA Main Achievements in NA and LAC Countries - Rekik, Mourad; Frija, Aymen; Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2023)
The presentation shows the main achievements of the IFAD-funded CLCA project in NA and LAC countries for the period April 2018 to June 2022. The presentation was delivered at the project's closing workshop held in Setif, Algeria, June 13-15, 2022.